Efektifitas Teknik Effleurage Massage Dan Slow Deep Breathing Dengan Teknik Endorphin Massage Terhadap Disminore - Sri Wulan Ratna Dewi; Dini Ariani; Hani Septiani (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2022)
The incidence of menstrual pain is 1,769,425,444 (90%), with 10-15% experiencing severe menstrual pain According to the World Health Organization (WHO). Menstrual pain in Indonesia is 54.89% primary menstrual pain and 9.36% secondary menstrual pain. Based on the findings, we found that in West Java 54.9% of women suffer from dysmenorrhea. Adolescent girls who experience menstrual pain have an impact, include impaired well-being, decreased activity, disturbed sleep patterns, disturbed appetite, disturbed interpersonal relationships, and difficulty concentrating on work and study. There are non-pharmacological pain management techniques: A combination of flirtation massage and slow deep breathing massage with endorphin massage techniques. The purpose of this study was to determine the effectiveness of combining dysmenorrhea massage and slow deep breathing massage techniques with endolphin massage techniques to reduce menstrual pain. This study used a semi-experimental design with pre- and post-test controls. The study design was using the quota sampling method on a sample of 32 people. The results of the independent sample test analysis provide a significance value of 0.233 for sig (both parties). This means it is greater than 0.05 (0.233> 0.005). The results of this test show that the t number is 1.218 and the t table is 2.042 (1218 <2.042), there is no significant difference between effleurage massage and slow deep breathing combined with endorphin massage to relieve menstrual pain. Both techniques are equally effective in relieving dysmenorrhea. Keywords: effleurage massage, slow deep breathing, endorphin massage, menstrual pain.